Social Cognition Analyzer Application—A New Method for the Analysis of Social Cognition in Patients Diagnosed With Schizophrenia - Varga, Eszter; Herold, Róbert; Tényi, Tamás; Endre, Szilvia; Fekete, Judit; Bugya, Titusz (Frontiers in Psychiatry, 2019)
Because of the importance of the assessment of social cognitive impairments in schizophrenia in clinical settings, a new computer application called SCAN (Social Cognition Analyzer applicatioN) was developed. Our first aim was to examine if schizophrenic individuals could be differentiated from healthy individuals based on the results of SCAN, taking into consideration both response rates and response times. Our second aim was to create Scanalizer, as part of SCAN, to produce social cognitive profiles of individual patients. 86 patients (SG) and 101 healthy participants (CG) were examined with SCAN. The experimental conditions were: ToM, irony, metaphor, emotion perception from prosody and social perception. SCAN displayed the tasks, recorded the answers and the response times. For the differentiation of the two groups a two-dimensional scatter plot was used. For the graphical presentation of the social cognitive profile of patients, the calculation of the distributions of CG’s results was made with Kolmogorov-Smirnov Goodness-of-fit Test and with the sum of squared residuals (SSR). We found that the SG’s response rates were significantly lower and the SG’s response times were significantly slower compared to the CG in every condition. With the two-dimensional comparison of the summary response rates and the summary response times of the participants, the SG could be differentiated from the CG and this differentiation worked irrespective of age and education. For the graphical representation of social cognitive functions of patients, distributions of the results of the CG were calculated. We found normal distributions in the response times of all conditions and in the response rates of the ToM condition. In the low-end tail of the irony condition, and in the metaphor, social perception and emotional prosody conditions, power-law distributions were found. We also found that the summary response rates of the lowest performing 10% of the CG was in the same range as the summary response rates of all examined patients. Scanalizer enables clinicians to measure and analyse individual schizophrenic patients’ social cognitive profiles. Moreover, SCAN could also be used to detect social cognitive disabilities of vulnerable individuals.